How do you factor \[{x^3} - 49x\].
Answer
Verified
442.8k+ views
Hint: Here we will factorize the given polynomial by using the factor theorem. Firstly we will find a value of \[x\] which satisfies the polynomial by hit and trial method. Then we will take that factor and divide the polynomial by it. Finally, we will factorize the quotient, which we obtained after dividing the polynomial and multiply it with the first factor to get the required answer.
Complete step-by-step answer:
We have to factorize polynomial \[{x^3} - 49x\]
First, we need to know at least one zero of the polynomial, so we will use the hit and trial method.
Let us check whether \[x = 0\] satisfies the polynomial or not
Putting \[x = 0\] in \[{x^3} - 49x\] we get,
\[{0^3} - 49 \times 0 = 0\]
So \[x = 0\] is a factor as it satisfies the polynomial.
So, one factor is \[\left( {x - 0} \right)\] or we can say \[x\] is a factor.
Now we will divide the polynomial \[{x^3} - 49x\] by \[x\] and take the common factor out from the polynomial. Therefore, we get
\[\dfrac{{{x^3} - 49x}}{x} = \dfrac{{x\left( {{x^2} - 49} \right)}}{x}\]
Cancelling out common terms, we get
\[ \Rightarrow \dfrac{{{x^3} - 49x}}{x} = \left( {{x^2} - 49} \right)\]
So we get our quotient as \[{x^2} - 49\].
Now we will factorize the obtained quotient \[{x^2} - 49\].
\[{x^2} - 49 = \left( {x - 7} \right)\left( {x + 7} \right)\]
To find the zeros we will put the above equation equal to zero.
\[\left( {x - 7} \right)\left( {x + 7} \right) = 0\]
\[\begin{array}{l} \Rightarrow \left( {x - 7} \right) = 0\\ \Rightarrow x = 7\end{array}\]
or
\[\begin{array}{l} \Rightarrow \left( {x + 7} \right) = 0\\ \Rightarrow x = - 7\end{array}\]
So, we get the zeroes of the given polynomial as \[x = 0\], \[x = 7\] and \[x = - 7\]
Hence, the factors of the polynomial are \[\left( x \right)\left( {x - 7} \right)\left( {x + 7} \right)\].
Note: Factor theorem states that if a polynomial \[f\left( x \right)\] of degree\[n \ge 1\] and ‘\[a\]’ is any real number then, if \[f\left( a \right) = 0\] then only \[\left( {x - a} \right)\] is a factor of the polynomial. The two problems where Factor Theorem is usually applied are when we have to factorize a polynomial and also when we have to find the roots of the polynomial. It is also used to remove known zeros from a polynomial while leaving all unknown zeros intact. It is a special case of a polynomial remainder theorem.
Complete step-by-step answer:
We have to factorize polynomial \[{x^3} - 49x\]
First, we need to know at least one zero of the polynomial, so we will use the hit and trial method.
Let us check whether \[x = 0\] satisfies the polynomial or not
Putting \[x = 0\] in \[{x^3} - 49x\] we get,
\[{0^3} - 49 \times 0 = 0\]
So \[x = 0\] is a factor as it satisfies the polynomial.
So, one factor is \[\left( {x - 0} \right)\] or we can say \[x\] is a factor.
Now we will divide the polynomial \[{x^3} - 49x\] by \[x\] and take the common factor out from the polynomial. Therefore, we get
\[\dfrac{{{x^3} - 49x}}{x} = \dfrac{{x\left( {{x^2} - 49} \right)}}{x}\]
Cancelling out common terms, we get
\[ \Rightarrow \dfrac{{{x^3} - 49x}}{x} = \left( {{x^2} - 49} \right)\]
So we get our quotient as \[{x^2} - 49\].
Now we will factorize the obtained quotient \[{x^2} - 49\].
\[{x^2} - 49 = \left( {x - 7} \right)\left( {x + 7} \right)\]
To find the zeros we will put the above equation equal to zero.
\[\left( {x - 7} \right)\left( {x + 7} \right) = 0\]
\[\begin{array}{l} \Rightarrow \left( {x - 7} \right) = 0\\ \Rightarrow x = 7\end{array}\]
or
\[\begin{array}{l} \Rightarrow \left( {x + 7} \right) = 0\\ \Rightarrow x = - 7\end{array}\]
So, we get the zeroes of the given polynomial as \[x = 0\], \[x = 7\] and \[x = - 7\]
Hence, the factors of the polynomial are \[\left( x \right)\left( {x - 7} \right)\left( {x + 7} \right)\].
Note: Factor theorem states that if a polynomial \[f\left( x \right)\] of degree\[n \ge 1\] and ‘\[a\]’ is any real number then, if \[f\left( a \right) = 0\] then only \[\left( {x - a} \right)\] is a factor of the polynomial. The two problems where Factor Theorem is usually applied are when we have to factorize a polynomial and also when we have to find the roots of the polynomial. It is also used to remove known zeros from a polynomial while leaving all unknown zeros intact. It is a special case of a polynomial remainder theorem.
Recently Updated Pages
Master Class 9 General Knowledge: Engaging Questions & Answers for Success
Master Class 9 English: Engaging Questions & Answers for Success
Master Class 9 Science: Engaging Questions & Answers for Success
Master Class 9 Social Science: Engaging Questions & Answers for Success
Master Class 9 Maths: Engaging Questions & Answers for Success
Class 9 Question and Answer - Your Ultimate Solutions Guide
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.